Optimization of Micro Resistance Spot Welding Parameters to Maximum Load, Fracture Area, and Nugget Thickness on AA1100 Using Response Surface Method - Muzakki, Hakam; Sunar Baskoro, Ario; Kiswanto, Gandjar; ., Winarto (International Journal of Engineering and Technology, 2018)
An improvement of micro welding technology is needed to support assembly of small components. The parameters of the micro resistance spot welding (ÂµRSW) lead to welding quality such as maximum load, fracture area, and nugget thickness, some of welding quality parameters. There are not many researchers studying the welding quality of ÂµRSW. This study aims to optimize welding parameters into maximum load, fracture area, and nugget thickness. The optimization of welding parameters used the response surface method (RSM). The highest value of maximum load 276.8 N could be achieved when welding current and welding time are 2 kA and 1 CT. The welding time on 1CT and welding current on around 1.5 kA can optimize to obtain the maximum load 200 N. 1 CT welding time or more and welding current near 3 kA result more 8 mm2 of fracture area. The thinnest and the thickest of the nugget were 0.553 mm when 1.5 CT of the welding time and 2 kA of welding current, and 0.790 mm when the welding time on 0.5 CT and welding current 1 kA. The value of nugget thickness optimize when the welding current between 1.5 kA and 0.5 kA, the magnitude of welding time less than 1 CT.Â